Acidogenicity of dual-species biofilms of bifidobacteria and Streptococcus mutans - de Matos, Bruno Mello [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Do, Thuy; Beighton, David; Koga-Ito, Cristiane Yumi [UNESP] (My University, 2017)
Objective: The aim of this study was to evaluate the acidogenicity of dual-species biofilms of bifidobacteria and Streptococcus mutans. Materials and methods: The following strains were tested: Bifidobacterium dentium DSM20436, Parascardovia denticolens DSM10105, and Scardovia inopinata DSM10107. Streptococcus mutans UA159 and Lactobacillus acidophilus ATCC4356 were used as control. Bifidobacteria were studied planktonically as they were not able to form monospecies biofilm, they were grown in biofilms associated with S. mutans. Endogenous polysaccharide reserves of cultures at log phase were depleted. Standardized suspensions of the microorganisms were incubated in growth media supplemented with 10 mM glucose, lactose, raffinose, glucose, or xylitol. S. mutans biofilms were grown on glass cover slips for 24 h to which bifidobacteria were added. After 24 h, the dual-species biofilms were exposed to the same carbon sources, and after 3 h, the pH of spent culture media and concentrations of organic acids were measured. Statistical analyses were carried out using ANOVA and Tukey’s test (α = 0.05). Results: A higher pH drop was observed when S. mutans was associated with P. denticolens or S. inopinata, in either planktonic or biofilm cultures, than with S. mutans alone. Bifidobacteria showed a higher pH drop in the presence of raffinose than S. mutans or L. acidophilus. Conclusions: Dual-species biofilms of bifidobacteria and S. mutans produced more acid and greater pH drops than biofilms of S. mutans alone. Clinical relevance: New insights on the complex process of caries pathogenicity contribute to the establishment of preventive and therapeutic measures, in particular in specific cases, such as in early childhood caries.
Keywords: Acidogenicity; Bifidobacteria; Biofilms; Dental caries